Onychiuridae (Collembola) of Australia: a key to species with notes on their distributions and pest status. Issue 2 (30th May 2022) - Greenslade, Penelope; Ireson, John
Abstract: The onychiurid fauna of Australia is revised and found to comprise six species belonging to five genera. All species are already described and are widespread in the Northern Hemisphere so they are considered to be introduced to Australia. For the most part, they are only known in Australia from agricultural and horticultural soils and home gardens as well as worm beds. A dichotomous key to the species is presented together with updated names, relevant synonymies, a brief description of each and comments on their distribution and ecology. The six species separated in the key are Protaphorura fimata (Gisin, 1952), Thalassaphorura encarpata (Denis, 1931), Thalassaphorura cryptopyga (Denis, 1931), Orthonychiurus folsomi (Schäffer, 1900), Deuteraphorura cebennaria (Gisin, 1956) and Onychiurus ambulans (Linnaeus, 1758). A seventh species is listed here but in family Tullbergiidae, Metaphorura affinis (Börner, 1902). It is included as it could be confused with the Onychiurinae in the field. In Australia and overseas, onychiurids have been associated with root damage to plants in home gardens and field crops, and we discuss their pest status using data from assessments of field crop damage in Australia. The aim of this paper is to provide an identification guide to field workers so that they can decide whether control methods are required.